Cancer Chemoprevention: Preclinical In Vivo Alternate Dosing Strategies to Reduce Drug Toxicities. (24th April 2019) - Mohammed, Altaf; Fox, Jennifer T; Miller, Mark Steven
Abstract: Cancer chemopreventive agents inhibit the formation of precursor lesions and/or the progression of these lesions to late stage disease. This approach to disease control has the potential to reduce the physical and financial costs of cancer in society. Several drugs that have been approved by the FDA for other diseases and have been extensively evaluated for their safety and pharmacokinetic/pharmacodynamic characteristics have the potential to be repurposed for use as cancer chemopreventive agents. These agents often mechanistically inhibit signaling molecules that play key roles in the carcinogenic process. The safety profile of agents is a primary concern when considering the administration of drugs for chemoprevention, as the drugs will be given chronically to high-risk, asymptomatic individuals. To decrease drug toxicity while retaining efficacy, several approaches are currently being explored. In this short review, we describe studies that use preclinical in vivo models to assess efficacy of alternative drug dosing strategies and routes of drug administration on chemopreventive drug efficacy. In vivo drug dosing strategies that reduce toxicity while retaining efficacy will pave the way for future cancer prevention clinical trials.